Compact Source Detection in Multichannel Microwave Surveys: From SZ Clusters to Polarized Sources - Diego Herranz; Francisco Argüeso; Pedro Carvalho (Advances in Astronomy)
We describe the state-of-the art status of multifrequency detection techniques for compact sources in microwave astronomy. From the simplest cases where the spectral behaviour is well known (i.e., thermal SZ clusters) to the more complex cases where there is little a priori information (i.e., polarized radio sources) we will review the main advances and the most recent results in the detection problem.